2007
DOI: 10.1111/j.1460-2695.2007.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength recovery of machined Al2O3/SiC composite ceramics by crack healing

Abstract: A B S T R A C T Alumina is used in various fields as a machine component. However, it has a low fracture toughness, which is a weakness. Thus, countless cracks may be initiated randomly by machining, and these cracks decrease the component's mechanical properties and reliability.To overcome this problem, a crack-healing ability could be a very useful technology. In this study, Al 2 O 3 /SiC composite was sintered. This alumina exhibits excellent crackhealing ability. Small specimens for a bending test were mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In response to crack‐healing treatment at 1400°C for 10 h, the machined specimens exhibited the same strength as the nonmachined specimens. Similar behavior has been observed in Al 2 O 3 /SiC 9,10 and Mullite/SiC 8 composites. These results indicate that crack‐healing treatment is the most effective method for increasing reliability and is the best substitution for costly precision machining processes.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…In response to crack‐healing treatment at 1400°C for 10 h, the machined specimens exhibited the same strength as the nonmachined specimens. Similar behavior has been observed in Al 2 O 3 /SiC 9,10 and Mullite/SiC 8 composites. These results indicate that crack‐healing treatment is the most effective method for increasing reliability and is the best substitution for costly precision machining processes.…”
Section: Introductionsupporting
confidence: 84%
“…To overcome this problem, many researchers have studied the relationship between machining conditions and damage to identify the optimized machining condition that introduces only acceptable surface damages 2,3,6 . Alternatively, some researchers have attempted to develop more economical means of self‐crack‐healing for machining damage 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…The oxidation products were Ti 2 AlC and Ti 2 SnC. The crack-healing behavior of Al 2 O 3 / SiC composite was investigated under various conditions by Ono et al 48 The healing process was accomplished through the sintering of the composites. The heat treatment conditions to heal the cracks completely ranged from (1000°C-1400°C) in air.…”
Section: Ceramics Thin Films and Its Composites/ Concepts And Previmentioning
confidence: 99%
“…Systems like Si 3 N 4 /SiC, Mullite/SiC, and Al 2 O 3 / SiC have been investigated and showed significant selfhealing abilities. 19,48,55 The crack-healing behavior in Al 2 O 3 was investigated by Kim et al 56 Their results showed that cracks can be healed by sintering the samples above 1400°Ϲ for 1 hour. The crack-healing behavior of Cr 2 AlC ceramic as a function of temperature, time, and crack size was investigated by Li et al 57 In their study they showed that healing of the cracks was due to annealing of the specimens at temperatures above 1000°C.…”
Section: Ceramics Thin Films and Its Composites/ Concepts And Previmentioning
confidence: 99%
“…On the other hand, numerous studies reported the effectiveness of SiC particles as a healing agent. Some of the common composites are SiC/ Al 2 O 3 [16], SiC/Si 3 N 4 [17], SiC/ZrB 2 [18] and SiC/Al 6 Si 2 O 13 [19], to name a few. At high enough temperature, SiC reacts with oxygen and produce SiO 2 which is accompanied with almost 81% volume expansion.…”
Section: Introductionmentioning
confidence: 99%